Microbial communities in riparian soils of a settling pond for mine drainage treatment. (1st June 2016) - Fan, Miaochun; Lin, Yanbing; Huo, Haibo; Liu, Yang; Zhao, Liang; Wang, Entao; Chen, Weimin; Wei, Gehong
Abstract: Mine drainage leads to serious contamination of soil. To assess the effects of mine drainage on microbial communities in riparian soils, we used an Illumina MiSeq platform to explore the soil microbial composition and diversity along a settling pond used for mine drainage treatment. Non-metric multidimensional scaling analysis showed that the microbial communities differed significantly among the four sampling zones (influent, upstream, downstream and effluent), but not seasonally. Constrained analysis of principal coordinates indicated heavy metals (zinc, lead and copper), total sulphur, pH and available potassium significantly influenced the microbial community compositions. Heavy metals were the key determinants separating the influent zone from the other three zones. Lower diversity indices were observed in the influent zone. However, more potential indicator species, related to sulphur and organic matter metabolism were found there, such as the sulphur-oxidizing genera Acidiferrobacter, Thermithiobacillus, Limnobacter, Thioprofundum and Thiovirga, and the sulphur-reducing genera Desulfotomaculum and Desulfobulbus ; the organic matter degrading genera, Porphyrobacter and Paucimonas, were also identified. The results indicated that more microorganisms related to sulphur- and carbon-cycles may exist in soils heavily contaminated by mine drainage. Graphical abstract: Highlights: We analysed the microbial composition of mine drainage-contaminated soils. The microbial communities shifted with the mine drainage flow direction. Heavy metals (Zn, Pb, Cu) were the key determinants of the microbial communities. Sulphur and organic matter metabolizing indicator species were identified.